The legal good protected by the Chilean antitrust legislation - Peralta Fierro, Ignacio (2022)
First, I argue that the Chilean debate regarding which is the legal good protected by our antitrust legislation suffers from certain defects: the adoption of an argumentative canon foreign to our continental tradition of law, as well as an analysis that follow from positive law. Second, I explain why these traits are defective. Third, I defend an alternative methodology to identify the protected legal good. Fourth, I apply said methodology.